Recent advances to enhance the immunomodulatory potential of mesenchymal stem cells - Sarsenova, Madina; Kim, Yevgeniy; Raziyeva, Kamila; Kazybay, Bexultan; Ogay, Vyacheslav; Saparov, Arman (Frontiers in Immunology, 2022)
Considering the unique therapeutic potential of mesenchymal stem cells (MSCs), including their immunosuppressive and immunomodulatory properties as well as their ability to improve tissue regeneration, these cells have attracted the attention of scientists and clinicians for the treatment of different inflammatory and immune system mediated disorders. However, various clinical trials using MSCs for the therapeutic purpose are conflicting and differ from the results of promising preclinical studies. This inconsistency is caused by several factors such as poor migration and homing capacities, low survival rate, low level of proliferation and differentiation, and donor-dependent variation of the cells. Enhancement and retention of persistent therapeutic effects of the cells remain a challenge to overcome in MSC-based therapy. In this review, we summarized various approaches to enhance the clinical outcomes of MSC-based therapy as well as revised current and future perspectives for the creation of cellular products with improved potential for diverse clinical applications.